Validation of the 2018 FIGO cervical cancer staging system - Matsuo, Koji; Machida, Hiroko; Mandelbaum, Rachel S.; Konishi, Ikuo; Mikami, Mikio (Gynecologic oncology, 2019)
To validate the revised 2018 International Federation of Gynecology and Obstetrics (FIGO) staging system for cervical cancer, with a particular focus on stage IB and stage III disease. Two retrospective cohort studies were conducted using The Surveillance, Epidemiology, and End Results Program between 1988 and 2014. The stage IB cohort consisted of node-negative FIGO stage IB1 (tumor size <2 cm), IB2 (2–3.9 cm), and IB3 (≥4 cm) cervical cancer. The stage III cohort consisted of FIGO stage IIIA, IIIB, and stage IIIC1 (any pelvic nodal metastasis) cervical cancer. Multivariable analysis was performed for cause-specific survival based on cancer stage. In the stage IB cohort (n = 8909), stage IB1 tumors were more likely to be adenocarcinoma and low-grade compared to other the groups (P < 0.001). On multivariable analysis, stage IB2 disease was independently associated with a nearly two-fold increased risk of cervical cancer mortality compared to stage IB1 disease (adjusted-hazard ratio [HR] 1.98, 95% confidence interval [CI] 1.62–2.41, P < 0.001). In the stage III cohort (n = 11,733), stage IIIC1 was independently associated with improved cause-specific survival compared to stage IIIB disease (adjusted-HR 0.79, 95%CI 0.74–0.85, P < 0.001). Survival of stage IIIC1 disease significantly differed based on T = stage, (5-year rates: 74.8% for T1, 58.7% for T2, and 39.3% for T3) with a 35.3% difference in absolute survival (P < 0.001). The 2018 FIGO staging system for cervical cancer is useful to distinguish survival groups; stage IB1 and stage IB2 disease have distinct characteristics and survival outcomes, while survival in stage IIIC1 varies depending on local tumor factors. FIGO revised cervical cancer staging in 2018•Revised staging was validated in a population-based tumor registry.•Stage IB1 and IB2 disease have distinct tumor characteristics and survival.•Stage IIIC1 disease has superior survival compared to stage IIIA-B disease.•Survival of stage IIIC1 disease depends on local tumor factors.